The Riddle of Literary Quality A Computational Approach - van Dalen-Oskam, Karina (Amsterdam University Press, 2023)
What is literature? Can we measure 'literariness' in texts themselves? The innovative Computational Humanities project The Riddle of Literary Quality asked thousands of Dutch readers for their opinion about contemporary Dutch and translated novels. The public shared which novels they had read, what they really thought of them, and how they judged their quality. Their judgments of the same novels were compared with the results of computational analysis of the books. Using evidence from almost 14,000 readers and building on more textual data than ever before, Van Dalen-Oskam and her team uncovered unconscious biases that shed new light on prejudices many people assumed no longer existed. This monograph explains in an accessible way how the project unfolded, which methods were used, and how the results may change the future of Literary Studies.